Facial Growth at 5 and 10 Years After Veau-Wardill-Kilner Versus Minimal-Incision Technique Repair of Isolated Cleft Palate. (January 2018) - Parikakis, Konstantinos; Larson, Ola; Larson, Margareta; Karsten, Agneta
Objective: To compare the Veau-Wardill-Kilner technique with the Minimal-Incision technique repair of isolated clefts of the hard and soft palate regarding facial growth at 5 and 10 years of age. Design: Retrospective study of lateral cephalograms. Setting: Hospital and university based. Patients: A consecutive series of 145 Caucasian nonsyndromic children born with isolated cleft palate between 1980 and 1996 were studied. Children with Pierre Robin sequence (PRS) were included in the study. The patients were divided into 4 groups: 2 groups regarding surgical technique and 2 groups regarding cleft length. Intervention: Veau-Wardill-Kilner or Minimal-Incision palatoplasty. Main Outcome Measures: Eleven skeletal and 1 soft tissue measurement were evaluated from lateral cephalograms taken at 5 and 10 years of age. Results: Only minor differences in cephalometric morphology were found between the Veau-Wardill-Kilner technique group and the Minimal-Incision technique group. Similar results were found independent of cleft length or the inclusion of PRS in the sample. Conclusion: The craniofacial cephalometric morphology at 5 and 10 years of age in patients with isolated cleft palate is similar between the Veau-Wardill-Kilner and the Minimal-Incision technique group.